FERGANA VALLEY: FORMS OF THE MASTER INITIATION RITE (Scientific journal of the Fergana State University, 2023)
The ustod-shogird system is the most stable social institution in the field of handicrafts. The final stage of training is the ceremony "fatah ukish", "fatah berish" among the Turkic population of the Fergana Valley, "kamar baste" - among the Tajik. In any of these rituals, after the completion of certain solemn actions, the neophyte (initiate) receives a new status, evidence of his belonging to the corresponding social group.